The steadfast and the wavered in Monica Ali’s Brick Lane and Aboulela’s the Translator - Rokhman, Muh Arif; Dzikriyya, Shafira Ainun (Universitas Islam Sultan Agung, 2025)
People from the colonized countries in the past moved to the United Kingdom to seek better lives. The researched novels depict this with the main characters of two different Muslim women. They must maintain their Islamic values while also adapting to English lifestyles and social relationships. The objective of the research is to identify patterns relating to how the concept of istiqamah (holding fast to Islamic principles) was practiced by Muslim woman characters in two novels, namely Brick Lane and The Translator, as well as the challenges faced by these characters in the novels. The research, being qualitative research, took the data from the two literary works in the form of primary data. The secondary data was taken from reviews of novels and other books. . Analysis of data was conducted by taking the excerpts from the novel being relevant to the theoretical concepts. The theory used is comparative literature, that is the application of religious concept(s) to literary works. The results showed that two different patterns in holding to istiqamah can be observed; one character is still steadfast in the principle, while the other changes. Future researchers are encouraged to conduct research by adding more novels having the same themes.